2012
DOI: 10.1016/j.hrthm.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter-defibrillator FDA safety advisories: Impact on patient mortality and morbidity

Abstract: Background A significant proportion of implantable cardioverter-defibrillators (ICDs) have been subject to FDA advisories. The impact of device advisories on mortality or patient care is poorly understood. Although estimated risks of ICD generators under advisory are low, dependency on ICD therapies to prevent sudden death justifies assessment of long-term mortality. Objective To test association of FDA advisory status with long-term mortality. Methods The study was a retrospective, single-center review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Though there were no major complications attributed to these alerts, the patient burden related to extra visits or procedures did lead to an increased cost burden. Additional studies confirmed the high volume of patients affected, though there continued to be no evidence of associated of increased mortality 174 . Acknowledging these challenges, in 2005 the HRS and the FDA convened a conference on PM and ICD performance.…”
Section: Section 11 Manufacturer Responsibilities With Remote Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there were no major complications attributed to these alerts, the patient burden related to extra visits or procedures did lead to an increased cost burden. Additional studies confirmed the high volume of patients affected, though there continued to be no evidence of associated of increased mortality 174 . Acknowledging these challenges, in 2005 the HRS and the FDA convened a conference on PM and ICD performance.…”
Section: Section 11 Manufacturer Responsibilities With Remote Monitoringmentioning
confidence: 99%
“…Additional studies confirmed the high volume of patients affected, though there continued to be no evidence of associated of increased mortality. 174 Acknowledging these challenges, in 2005 the HRS and the FDA convened a conference on PM and ICD performance. The resulting taskforce called for improved communication from manufacturers to physicians and patients regarding recalls and advisories, and generally more cooperation among industry, the FDA, and the physician community.…”
Section: Section 11 Manufacturer Responsibilities With Remote Monitoringmentioning
confidence: 99%
“…The apparent paradox of more advisories despite improving overall performance is consistent with a lower tolerance of malfunctions at multiple levels. Thus, a recent study of 1,644 consecutive ICD implants between 1996 and 2004 revealed that 704 patients(43 %) were part of an advisory, but only 28 of 1,644 patients (1.7 %) actually had an advisory-related device malfunction, and Class I recalls were not associated with increased mortality [17]. Some patients did undergo device replacement (42/1,644, 2.5 %) and hence were harmed, but it should also be considered that ultimately, if the patient does not succumb to comorbidities, that most ICDs need to be replaced and that this is a fractional harm depending on the device age when replaced.…”
Section: The Us Regulatory Framework and Innovationmentioning
confidence: 99%
“…52 Additionally, up to 40 % of leads or generators implanted in patients are affected by FDA safety advisories. 53 54 Device and lead failure often require lead extraction.…”
Section: Generator and Lead Failures/recallsmentioning
confidence: 99%